2021
DOI: 10.1088/1742-6596/1764/1/012167
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Porous Asphalt Mixture by Using a Bottom Ash Boiler as a Filler

Abstract: Porous asphalt is asphalt mixture using open gradation dominated by coarse aggregate to produce a large enough cavity. Bottom ash waste produced by a boiler used in the extraction process of palm oil into crude palm oil. Shells and pulps that has been burned at high temperature between 500°C to 700°C will later become of boiler bottom ash. The aim of this study was to inspect the performance of Porous Asphalt Mixture characteristics which combining bottom ash boiler and cement as filler using Retona Blend 55 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results showed that the modified mixtures enhanced the binder draindown as it decreased from 0.3% for the conventional porous mixtures to 0.08%, but the presence of clay brick dust resulted in a reduction in the ability of resisting the rutting 8 . A Bottom Ash boiler was investigated as filler to the porous asphalt mixture with cement and it was concluded that a 6% asphalt content with a variation of filler 50% cement and 50% bottom ash boiler met the Australian Asphalt Pavement Association AAPA 2004 Specifications 9 . Porous asphalt mixture stabilized by cellulose fibers was investigated and it was concluded that it had the same performance as porous asphalt mixture stabilized by mineral fibers and with addition of 0.3% cement dust, it could present a higher performance 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the modified mixtures enhanced the binder draindown as it decreased from 0.3% for the conventional porous mixtures to 0.08%, but the presence of clay brick dust resulted in a reduction in the ability of resisting the rutting 8 . A Bottom Ash boiler was investigated as filler to the porous asphalt mixture with cement and it was concluded that a 6% asphalt content with a variation of filler 50% cement and 50% bottom ash boiler met the Australian Asphalt Pavement Association AAPA 2004 Specifications 9 . Porous asphalt mixture stabilized by cellulose fibers was investigated and it was concluded that it had the same performance as porous asphalt mixture stabilized by mineral fibers and with addition of 0.3% cement dust, it could present a higher performance 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The test results show the increasing levels of LLDPE, the higher the stability value [4]. Another research that has been carried out is the use of 50% bot-tom ash and 50% cement as a filler with retona blend 55 as a binder in a porous asphalt mixture [5] [1]. To produce a mixture that meets the requirements, high quality asphalt with a high softening point is needed [6].…”
Section: Introductionmentioning
confidence: 99%